Differentiation of human adipose derived stem cells into Leydig‐like cells with molecular compounds. Issue 9 (10th July 2019) - Chen, Yong; Li, Chao; Ji, Weiping; Wang, Long; Chen, Xianwu; Zhao, Shenzhi; Xu, Zhangye; Ge, Renshan; Guo, Xiaoling
Abstract: Leydig cells (LCs) are the primary source of testosterone in the testis, and testosterone deficiency caused by LC functional degeneration can lead to male reproductive dysfunction. LC replacement transplantation is a very promising approach for this disease therapy. Here, we report that human adipose derived stem cells (ADSCs) can be differentiated into Leydig‐like cells using a novel differentiation method based on molecular compounds. The isolated human ADSCs expressed positive CD29, CD44, CD59 and CD105, negative CD34, CD45 and HLA‐DR using flow cytometry, and had the capacity of adipogenic and osteogenic differentiation. ADSCs derived Leydig‐like cells (ADSC‐LCs) acquired testosterone synthesis capabilities, and positively expressed LC lineage‐specific markers LHCGR, STAR, SCARB1, SF‐1, CYP11A1, CYP17A1, HSD3B1 and HSD17B3 as well as negatively expressed ADSC specific markers CD29, CD44, CD59 and CD105. When ADSC‐LCs labelled with lipophilic red dye (PKH26) were injected into rat testes which were selectively eliminated endogenous LCs using ethylene dimethanesulfonate (EDS, 75 mg/kg), the transplanted ADSC‐LCs could survive and function in the interstitium of testes, and accelerate the recovery of blood testosterone levels and testis weights. These results demonstrated that ADSCs could be differentiated into Leydig‐like cells by few defined molecular compounds, which might lay the foundation for further clinical application of ADSC‐LC transplantation therapy.